“Aprovechamiento sistémico de la pulpa de café como residuo agrícola y tratamiento de las aguas mieles por biorremediación en el alto mayo”-2014” - Azabache Liza, Yrwin Francisco (2014)
The first phase consisted of removing and reducing non-reducing sugars and tannins. By anaerobic fermentation processes in a bioreactor BATCH type agitator, far preparing alcohols. The second phase addressed the honey water treatment; bioremediation using a model of effective microorganisms (EM) and aquatic macrophytes was used. Under the study conditions 18.8 g of reducing sugars per liter Totals were obtained from the dried pulp and 2.0% bioethanol per liter of wine. Gallic acid was obtained as primary and most abundant polyphenols in a concentration of 4555.2 mg / kg of dry pulp. Regarding treatment of honey water results BOD and COD decreased, not reaching below the LMP, the STS is able to reduce below the LMP, the pH is within the range of the LMP, the temperature is below the LMP, like nitrates. Thus, it was concluded that it is possible, first use and transform agricultura! waste coffee to add value hoiisticaily, and on the other hand reduce the negative impacts on the environment generated by the wastewater.